Genome-wide polygenic risk score for retinopathy of type 2 diabetes. Issue 10 (10th March 2021) - Forrest, Iain S; Chaudhary, Kumardeep; Paranjpe, Ishan; Vy, Ha My T; Marquez-Luna, Carla; Rocheleau, Ghislain; Saha, Aparna; Chan, Lili; Van Vleck, Tielman; Loos, Ruth J F; Cho, Judy; Pasquale, Louis R; et al.
Abstract: Diabetic retinopathy (DR) is a common consequence in type 2 diabetes (T2D) and a leading cause of blindness in working-age adults. Yet, its genetic predisposition is largely unknown. Here, we examined the polygenic architecture underlying DR by deriving and assessing a genome-wide polygenic risk score (PRS) for DR. We evaluated the PRS in 6079 individuals with T2D of European, Hispanic, African and other ancestries from a large-scale multi-ethnic biobank. Main outcomes were PRS association with DR diagnosis, symptoms and complications, and time to diagnosis, and transferability to non-European ancestries. We observed that PRS was significantly associated with DR. A standard deviation increase in PRS was accompanied by an adjusted odds ratio (OR) of 1.12 [95% confidence interval (CI) 1.04–1.20; P  = 0.001] for DR diagnosis. When stratified by ancestry, PRS was associated with the highest OR in European ancestry (OR = 1.22, 95% CI 1.02–1.41; P  = 0.049), followed by African (OR = 1.15, 95% CI 1.03–1.28; P  = 0.028) and Hispanic ancestries (OR = 1.10, 95% CI 1.00–1.10; P  = 0.050). Individuals in the top PRS decile had a 1.8-fold elevated risk for DR versus the bottom decile ( P  = 0.002). Among individuals without DR diagnosis, the top PRS decile had more DR symptoms than the bottom decile ( P  = 0.008). The PRS was associated with retinal hemorrhage (OR = 1.44, 95% CI 1.03–2.02; P  = 0.03) and earlier DR presentation (10% probability of DR by 4 years in the top PRS decile versus 8 years in the bottom decile). These results establish the significant polygenic underpinnings of DR and indicate the need for more diverse ancestries in biobanks to develop multi-ancestral PRS.